The Measurement of National Wealth: Discussion - Gilbert, Milton; Clark, Colin; Stone, J. R. N.; Perroux, Francois; Lieu, D. K.; Evelpides; Divisia, Francois; Tinbergen; Kuznets; Smithies; Shirras; MacGregor (Econometrica, 1949)
Milton Gilbert, Colin Clark, J. R. N. Stone, Francois Perroux, D. K. Lieu, Evelpides, Francois Divisia, Tinbergen, Kuznets, Smithies, Shirras, MacGregor, The Measurement of National Wealth: Discussion, Econometrica, Vol. 17, Supplement: Report of the Washington Meeting (Jul., 1949), pp. 255-272